Six-component synthesis and biological activity of novel spiropyridoindolepyrrolidine derivatives: A combined experimental and theoretical investigation - Hossaini, Zinatossadat; Mohammadi, Marziyeh; Sheikholeslami-Farahani, Fatemeh (Frontiers in Chemistry, 2022)
The Petasites hybridus rhizome water extract was used as green media for the preparation of the Ag/Fe3O4/CdO@MWCNTs magnetic nanocomposites and its activity was evaluated by using in the one-pot multicomponent reaction of isatins, acetyl chloride, secondary amines, vinilidene Melderum’s acid, primary amines and malononitrile in aqueous at room temperature for the production of novel derivatives of spiropyridoindolepyrrolidine in excellent yields. Moreover, reduction of organic pollutants such 4-nitrophenol (4-NP) was performed by synthesized Ag/Fe3O4/CdO@MWCNTs in water at room temperature. The outcomes showed this catalyst was decreased organic pollutants in few seconds. The synthesized spiropyridoindolepyrrolidine have NH2 functional group that have acidic hydrogen and show high antioxidant activity. These synthesized compounds also displayed antimicrobial activity by using the disk diffusion procedure and two Gram-positive and Gram-negative bacteria. Also, to better understanding reaction mechanism density functional theory based quantum chemical methods have been applied. The employed process for production of spiropyridoindolepyrrolidine has some benefits such as short time of reactions, excellent efficiency of product, easy separation of catalyst and products.